Development Of A Game-Based Assessment Application On The Concept Of Momentum And Impulse (GAMBAS MIE) - Prima Warta Santhalia; Morris David Hukunala; Marmi Sudarmi (Universitas Lambung Mangkurat, 2024)
Misinterpretation of questions is one of the causes of low student learning outcomes. This study aims to address this issue by developing a Game-Based Assessment application on the subject of momentum and impulse, which includes illustrations and animations for each concept explanation and question. This study uses the 4D method (Define, Design, Development, and Disseminate). The 4D development model includes four stages: (1) Define - literature study, curriculum analysis, and student concept analysis; (2) Design - creation of the game application storyboard; (3) Development - development of the game-based assessment application followed by expert validation and limited trials, with data analyzed using qualitative and quantitative descriptive techniques; and (4) Disseminate - widespread distribution of the game-based assessment application in the form of copyright. The developed game-based assessment received positive responses from students, with an N-Gain value reaching 0.86 in the high category, indicating that the game-based assessment can improve students' conceptual mastery on the topic of momentum and impulse.